PENGEMBANGAN SUMBER DAYA MANUSIA PENGURUS MUI KABUPATEN BOGOR - Tohir, M. Abdullah; Rahmawati, Rita; Iskandar, Abubakar (Universitas Djuanda, 2021)
A Human Resource Development in semi-governmental organizations such as MUI is very important in the context of regeneration of leadership and management in the future period. The purpose of this study was to analyze the development of human resources for the Bogor Regency MUI management. The method used in this study is a qualitative method with a descriptive analysis approach to the population of the MUI Kab. Bogor numbered 188 members, then samples were taken using the Disproportionate Stratified Random Sampling technique, the data collection technique was a questionnaire technique, participatory observation, and structured and in-depth interviews. Then analyzed using the Weight Mean Score (WMS). The results showed that the development of human resources at the MUI Bogor Regency amounted to 4.78 with a very good interpretation. This is based on the results of observations and interviews with respondents from the MUI board of directors who said that the process of forming the organizational structure of the Regency MUI was carried out in deliberation by involving all related elements and all of these elements had the opportunity to have a career at the Regency MUI referring to the needs of the institution, which was very appropriate and by what was expected. So that the credibility of the institution's objectivity is maintained.